(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to define and measure the digital competence of female students in the kindergarten section according to the academic grade variable. To achieve the objectives of the research, the researchers built a digital competence scale, Basilotta et al.,2022consisting of (27) items, and the scale was applied to (150) female students from the kindergarten section, and for the four grades ( The first, second, third, and fourth), and the psychometric properties of the scale were extracted, represented by both types of validity (face validity and construct validity), and reliability was extracted using the Cronbach equation, and the reliability value reached (0.60), and it was concluded that there is digital competence among female students of the kindergarten department. Children, and depending on the grade, the digital proficiency of third-grade female students was higher than in the rest of the grades. In light of the research results, the researchers presented a number of recommendations and a set of proposals.